Mutual fund flow-performance relationship: the role of a foreign parent - Yuda, Li (2018)
In this paper we use a worldwide sample, including 31 countries, to test the influence of funds with a foreign parent on the flow-performance relationship. We study the reason behind the distinction in the way investors in different countries favor fund parents. We find that the flow-performance relationship is convex, consistent with previous studies using a worldwide sample. We also find that funds with foreign parents increase the convexity of fund flow to performance; in other words, investors buy more winners and sell less losers when funds have a foreign parent. The results also show that the enhanced convexity in funds with foreign parents is more pronounced in countries with less developed economies and financial markets, and where investors are less sophisticated.